De la tardor medieval al Renaixement: aspectes d'una gran mutació sociolingüística i cultural a través dels Viciana - Antoni Ferrando (Caplletra: Revista Internacional de Filologia, 2014)
Review and contextualisation of biographical, bibliographical, linguistic and ideological facets of Martí de Viciana el Vell (the elder) and his grandson Rafael Martí de Viciana (with special attention to linguistic attitude). By contrasting them, it serves to throw into relief the great cultural and sociolinguistic mutation in the heart of the classes dominating the kingdom of Valencia at the end of the 15th century and beginning of the 16th, caused by important political and social changes.